2013
DOI: 10.1117/12.2005896
|View full text |Cite
|
Sign up to set email alerts
|

Optical microscopy with super-resolution by liquid-immersed high-index microspheres

Abstract: We study super-resolution capability of liquid-immersed high refractive index (n~1.9-2.1) barium titanate glass microspheres with diameters from several microns up to hundreds of microns. Imaging is provided in a conventional upright microscope with the spheres placed in a contact position with various semiconductor and metallic nanostructures. Using a commercial Blu-ray disk, we demonstrate an ability to discern 100 nm feature sizes which cannot be resolved by conventional microscopy. Using silver nanowires w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…There is an extensive amount of works describing enhancement of resolution by the use of microspheres in various imaging systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In the geometric optics approach the dielectric microsphere behaves as a thin lens as the two principal planes of the microsphere optical system are coinciding at the center of the microsphere [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an extensive amount of works describing enhancement of resolution by the use of microspheres in various imaging systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In the geometric optics approach the dielectric microsphere behaves as a thin lens as the two principal planes of the microsphere optical system are coinciding at the center of the microsphere [19].…”
Section: Introductionmentioning
confidence: 99%
“…There is a certain interesting aspect about the use of microspheres for obtaining high resolutions which was not largely exploited. The measurements which have been made by the microspheres are usually based on light intensity measurement [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], so that all the information about the phases of the object, included in the evanescent waves are lost in the measurement process. Information about the phases of the object are especially important for imaging semi-transparent biological tissues for which one would like to learn about lateral changes in the tissue density.…”
Section: Introductionmentioning
confidence: 99%
“…However, the volatility of the ethanol solution was not conducive to a prolonged observation of the experiment. Darafsheh et al then demonstrated that super-resolution imaging can be achieved when high refractive index microspheres were completely submerged in a liquid solution [61,62]. Barium titanate (BaTiO 3 ) microspheres with a refractive index of 1.9 were completely submerged in an isopropyl alcohol solution with a refractive index of 1.37, and the super-resolution imaging of two-dimensional gold nanodimers comprising gold nanopillars with a diameter of 120 nm and height of 30 nm was achieved under an illumination light source with a wavelength of 550 nm.…”
Section: Types Of Microspheresmentioning
confidence: 99%
“…Optical properties of dielectric microspheres have attracted a tremendous interest recently because of the applications of these spheres in super-tight focusing [1][2][3][4] and super-resolution imaging [5][6][7][8][9] devices. Due to a possibility to reverse direction of propagation of light in the optical experiments these two properties are related 5 , however the mechanisms of supertight focusing (also termed "photonic nanojet" effects 1 ) and super-resolution effects still require further investigation.…”
Section: Introductionmentioning
confidence: 99%